Characterization of Biodegradable Plastic Nata De Soya Using Glycerol and Palm Oil Addictive Substances - Iryani Iryani; Iswendi Iswendi; Sri Benti Etika; Citra Devira; Regi Fadila Putra (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2021)
This research aimed to analyze the characterization of biodegradable plastic nata de soya (NDS). The addictive substance used to manufacture this plastic is a mixture of glycerol and palm oil with a saturated solution of arabic gum as an emulsifier. The volume variations are A (10:5:15) mL, B (10:10:30) mL, C (10:15:45) mL, control is (10 mL of 3% glycerol) and soaking time for NDS sheets with additives are 4, 6, and 8 days. The results showed that the highest degradation power of NDS is 87% in the variation of additive C with an immersion period of 8 days had a degree of crystallinity of 8.075%. The water resistance test was 318% in an immersion of NDS plastic with a variation of C for four days had a degree of crystallinity of 12.47%. The highest tensile strength value of plastic was 23.459 MPa in the composition of additive C with four days of immersion and had a degree of crystallinity of 13.172%.